Knotted urethral catheter: an unusual complication in adults - Jallad, Samer (BMJ Case Rep, 2017)
Knotting of feeding tubes or urinary catheters has been reported as a rare complication in paediatrics when draining the bladder. This is caused by inserting thin flexible tubes too far in, allowing it to coil. We present a case of a 70-year-old woman who was catheterised during a routine spinal surgery, and the catheter coiled and balloon failed to deflate requiring a cystostopic approach to puncture the balloon and remove it. Awareness of this complication in female catheterisation and education on length of catheter insertion is important to avoid this.